2016
DOI: 10.1155/2016/5265748
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Instantaneous Turbulent Flow Field in a 90-Degree Elbow Pipe with Circular Section

Abstract: Based on the special application of 90-degree elbow pipe in the HTR-PM, the large eddy simulation was selected to calculate the instantaneous flow field in the 90-degree elbow pipe combining with the experimental results. The characteristics of the instantaneous turbulent flow field under the influence of flow separation and secondary flow were studied by analyzing the instantaneous pressure information at specific monitoring points and the instantaneous velocity field on the cross section of the elbow. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…When the curvature radius changed from R = 1 h to R = 4 h, the wind flows opposite to the mainstream wind traces continued to reduce until they disappeared, and the final wind traces were basically parallel lines. Wang et al studied the instantaneous turbulent flow field of a 90° elbow and their results are similar to the results shown in Figure 3 [26]. In some cases, because there are a large number of opposite wind traces in the vortex, which are inconsistent with the main flow direction, the ventilation effect is significantly reduced.…”
Section: Resultsmentioning
confidence: 53%
“…When the curvature radius changed from R = 1 h to R = 4 h, the wind flows opposite to the mainstream wind traces continued to reduce until they disappeared, and the final wind traces were basically parallel lines. Wang et al studied the instantaneous turbulent flow field of a 90° elbow and their results are similar to the results shown in Figure 3 [26]. In some cases, because there are a large number of opposite wind traces in the vortex, which are inconsistent with the main flow direction, the ventilation effect is significantly reduced.…”
Section: Resultsmentioning
confidence: 53%
“…This is due to variations in hydrodynamic parameters such as wall shear stress and velocity at the elbow test section. Furthermore, the secondary flow and/or flow separation effect, which will lead to the generation of counterrotating vortexes, and various scale eddies at an elbow will disturb the flow pattern and promote the mass transfer process near the pipe wall [6,43,44]. The CFD simulation results discussed in the previous work was also indicated that the shear stress and velocity are different at various locations of the elbow test section [24].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, they found that LES reproduced the experimental profiles for the streamwise mean velocity and turbulent intensity just behind the elbow much better than RANS, while inside the bend both approaches yielded comparatively similar mean velocity profiles and pressure coefficients. Further FVM-based calculations of turbulent flow in 90 • elbows were presented by Dutta et al [29] and Wang et al [30].…”
Section: Introductionmentioning
confidence: 99%